2000
DOI: 10.1111/1467-9442.00185
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Shocks and Income Distribution: How did the Nordic Countries Fare during their Crises?

Abstract: Abstract:We analyse how inequality of disposable income evolved in Denmark, Finland, Norway and Sweden during the late 1980s and early 1990s when unemployment rose dramatically in all four countries. We find that a standard measure of inequality -the Gini coefficient -was surprisingly stable in all countries over this period. By decomposing the Gini coefficient into a number of income components, we can test hypotheses about the reasons for the stable income distribution. Our most straightforward hypothesis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 9 publications
(6 reference statements)
3
66
0
1
Order By: Relevance
“…In general, Norway has the institutional characteristics of the so-called 'Nordic model'. One important feature of this model is a centralized wage bargaining system that has produced a relatively compressed wage structure that has not changed much over time (Aaberge, Bjorklund and Smith (2000), Haegeland, Klette and Salvanes (1999), and Kahn (1998)). …”
Section: Introductionmentioning
confidence: 99%
“…In general, Norway has the institutional characteristics of the so-called 'Nordic model'. One important feature of this model is a centralized wage bargaining system that has produced a relatively compressed wage structure that has not changed much over time (Aaberge, Bjorklund and Smith (2000), Haegeland, Klette and Salvanes (1999), and Kahn (1998)). …”
Section: Introductionmentioning
confidence: 99%
“…Aaberge et al (1996) and Gottschalk and Smeeding (1997) reported a rather steep increase in the Gini coefficient of annual disposable incomes among individuals between 1986 and 1990; Aaberge et al (1997) reported a somewhat smoother increase in the Gini coefficient for the adult working-age population between 1987 and 1990. Estimates for the Gini coefficient for the population aged 18 and over indicate broad stability in the 1980s, and a slight decrease in the early 1990s (Danish Ministry of Finance, 1997).…”
mentioning
confidence: 95%
“…Estimates for the Gini coefficient for the population aged 18 and over indicate broad stability in the 1980s, and a slight decrease in the early 1990s (Danish Ministry of Finance, 1997). According to Aaberge et al (1997), the contribution of earnings to income inequality increased between 1986 and 1990.…”
mentioning
confidence: 99%
See 2 more Smart Citations